The effect of ARBOCEL® on the performance and health status of growing and finishing rabbit - Kovács-Weber, Mária; Abayné Hamar, Enikő; Zimborán, Ágnes; Balláné Erdélyi, Márta; Fazekas, Natasa; Heincinger, Mónika; Kustos, Károly; Nyíri, András; Szabó, Rubina; Gerber, Zsuzsanna; Gerber, Johann; Somodi, Brigitta (Animal welfare, Ethology and Housing Systems (AWETH), 2016)
A 6 week experiment (5-11 week) was conducted to study the effects of 0.8% and 1% ARBOCEL® inclusion of the diet on live weight, feed conversion ratio and mortality of rabbit. The same trends were observed in all experiments. The measured body weight values of the control group were higher than the treated group’s, throughout the experiment. Those rabbits that ate 0.8 % or 1% ARBOCEL® in their feed had higher feed conversion ratio than the control group. However, in the treated groups the mortality rate was below 1% throughout the study.
Keywords: Arbocel®; lignocellulose; growth; health